Disaster and Emergency Preparedness : Guidance for Schools - International Finance Corporation (World Bank, Washington, DC, 2014)
Communities around the world are faced with natural hazards-extreme environmental events such as floods, cyclones, earthquakes, fires, and tsunamis. For some communities, these natural hazards turn into disasters, resulting in tremendous losses and injuries for students, school staff and families. However, by taking preventative measures before hazard impact, and learning preparedness and response, a culture of safety can be fostered. Communities can reduce and even eliminate such losses. This handbook is aimed at administrators, teachers, support staff, and other individuals involved in emergency and disaster preparedness at schools. It seeks to: 1) guide administrators and staff in assessing risks and planning and carrying out physical protection measures; 2) develop skills and provisions for disaster and emergency preparedness, response, and rapid recovery; and 3) support schools in developing disaster and emergency plans specific to their local needs and reflecting good practices internationally and nationally.